Atividades experimentais em sala de aula de física baseadas na utilização da vídeo-análise e estruturadas a partir do Diagrama V - Trabach, Adriano Ricardo da Silva (2018)
The present work reports the use of Gowin's epistemological V, denominated in this work of Diagram V structuring the application of the video-analysis in experimental activities of Physics in a public state school in Espírito Santo, ES. The school where the work was carried out is the State School of Fundamental and Secondary Education São João Batista located in the Municipality of Cariacica, in the metropolitan area of Greater Victoria. It was developed four experimental activities of Physics with a class of the 1st year of high school, with students with 15 years on average. Activities were performed on Rectilinear and Uniform Motion, Rectilinear and Uniformly Varied Motion, Free Fall and Oblique Launching, with Diagram V being used as a structuring tool for the process of using video analysis, orientation, data collection and evaluation throughout the process. Diagrams V produced by the students were analysed according to the criteria proposed by Gowin and Alvarez (2005) and Prado (2015). The results revealed that Diagram V has proved to be a highly effective tool for structuring the application of video analysis for data acquisition, organization and analysis of experiments, allowing students to concisely and organized express their knowledge at the same time which reflect on the construction of one's own knowledge.